Screening Laboratory Testing in Asymptomatic Minor Pediatric Blunt Trauma Leads to Unnecessary Needle Sticks. Issue 12 (December 2021) - Badru, Faidah; Osei, Hector; Munoz-Abraham, Armando Salim; Saxena, Saurabh; Breeden, Robert; Piening, Nicholas; Starr, David; Xu, Perry; Greenspon, Jose; Fitzpatrick, Colleen M.; Villalona, Gustavo A.; Chatoorgoon, Kaveer
Abstract : Objective: Screening blood work after minor injuries is common in pediatric trauma. The risk of missed injuries versus diagnostic necessity in an asymptomatic patient remains an ongoing debate. We evaluated the clinical utility of screening blood work in carefully selected asymptomatic children after minor trauma. Methods: Patients seen at a level 1 pediatric center with "minor trauma" for blunt trauma between 2010 and 2015 were retrospectively reviewed. Exclusion criteria were age <4 of >18 years, a Glasgow Coma Scale score of <15, penetrating trauma, nonaccidental trauma, hemodynamic instability, abdominal findings (pain, distension, bruising, tenderness), hematuria, pelvic/femur fracture, multiple fractures, and operative intervention. Data abstraction included demographics, blood work, interventions, and disposition. Result: A total of 1308 patients were treated during the study period. Four hundred thirty-three (33%) met inclusion criteria. Mean ± SD age was 12.7 ± 4 years (range, 4–18 years), and 59% were male. Seventy-eight percent were discharged home from the emergency department. All patients had blood work. Twenty-eight percent had at least one abnormal laboratory value. The most common abnormal blood work was leukocytosis (16%). Thirty percent had an intervention, and none prompted by abnormal blood work. One patient had an intra-abdominal finding (psoas hematoma). Conclusion: When appropriately selected, screening laboratory testing in asymptomatic minor pediatric blunt trauma patients leads to unnecessary needle sticks without significant advantage.